Effects of a neurokinin-1 receptor antagonist in the acute phase after thoracic spinal cord injury in a rat model - Zheng, Guoli; Harms, Anna-Kathrin; Tail, Mohamed; Zhang, Hao; Nimmo, Alan; Skutella, Thomas; Kiening, Karl; Unterberg, Andreas; Zweckberger, Klaus; Younsi, Alexander (Frontiers in Molecular Neuroscience, 2023)
Objective: Disruption of the blood-spinal cord barrier (BSCB) with subsequent edema formation and neuroinflammation contributes to aggravation of spinal cord injury (SCI). We aimed to observe the effect of antagonizing the binding of the neuropeptide Substance-P (SP) to its neurokinin-1 (NK1) receptor in a rodent SCI model. Methods: Female Wistar rats were subjected to a T9 laminectomy with or without (Sham) a T9 clip-contusion/compression SCI, followed by the implantation of an osmotic pump for the continuous, seven-day-long infusion of the NK1 receptor antagonist N-acetyl tryptophan (NAT) or saline (Vehicle) into the intrathecal space. The animals were assessed via MRI, and behavioral tests were performed during the experiment. 7 days after SCI, wet & dry weight and immunohistological analyses were conducted. Results: SP inhibition via NAT showed limited effects on reducing edema. However, the invasion of T-lymphocytes and the number of apoptotic cells were significantly reduced with the NAT treatment. Moreover, a trend of reduced fibrinogen leakage, endothelial and microglial activation, CS-GAG deposition, and astrogliosis was found. Nevertheless, only insignificant general locomotion recovery could be observed in the BBB open field score and the Gridwalk test. In contrast, the CatWalk gait analysis showed an early onset of recovery in several parameters. Conclusion: Intrathecal administration of NAT might support the integrity of the BSCB in the acute phase after SCI, potentially attenuating aspects of neuroinflammation, reducing edema formation, and improving functional recovery.